We first consider a first-order ODE system composed of a set of
simultaneous first-order explicit ODEs:
![$\displaystyle y'_i(t)=f_i(t,\,y_1(t),\cdots,y_N(t))\;\;\;\;\;\;\;\;(i=1,\cdots,N)$](img281.svg) |
(109) |
The goal is to find the
functions
that
satisfy these
equations based on the
initial conditions
. This system can be represented
in vector form:
![$\displaystyle {\bf y}'(t)=\frac{d}{dt}{\bf y}(t)={\bf f}(t,\,y_1(t),\cdots,y_N(t))
={\bf f}(t,\,{\bf y}(t)),\;\;\;\;\;\;
{\bf y}(0)={\bf y}_0$](img285.svg) |
(110) |
where
![$\displaystyle {\bf y}(t)=\left[\begin{array}{c}y_1(t)\\ \vdots\\ y_N(t)\end{arr...
...{array}{c}f_1(t,\,{\bf y}(t))\\
\vdots\\ f_N(t,\,{\bf y}(t))\end{array}\right]$](img286.svg) |
(111) |
Consider as an example a special ODE system containing
first-order LCCODEs:
![$\displaystyle \frac{d}{dt}\left[\begin{array}{c}y_1(t)\\ \vdots\\ y_N(t)\end{ar...
...array}\right]
+\left[\begin{array}{c}x_1(t)\\ \vdots\\ x_N(t)\end{array}\right]$](img287.svg) |
(112) |
which can be expressed in matrix form as
or![$\displaystyle \;\;\;\;
{\bf y}'(t)-{\bf Ay}(t)={\bf x}(t)$](img289.svg) |
(113) |
First, to find the homogeneous solution when
,
we assume
and substitute this into
the ODE system to get:
![$\displaystyle {\bf y}'(t)=\lambda \,e^{\lambda t}{\bf v}={\bf A} e^{\lambda t}{\bf v}$](img292.svg) |
(114) |
Dividing both sides by
, we get the eigenequation of
:
![$\displaystyle {\bf Av}=\lambda {\bf v}$](img295.svg) |
(115) |
where
is an eigenvalue of
and
is the
corresponding eigenvector. In general, there are
eigenvalues
and
corresponding eigenvectors
for an
by
matrix
,
and the homogeneous solution is a linear combination of all
such
solutions:
![$\displaystyle {\bf y}_h(t)=\sum_{i=1}^N c_i e^{\lambda_it}{\bf v}_i
=[{\bf v}_1...
...array}{c} c_1\\ \vdots\\ c_N\end{array}\right]
={\bf V}e^{{\bf\Lambda}t}{\bf c}$](img300.svg) |
(116) |
where
is a matrix exponential function, which
is generally defined based on the Taylor expansion of an
exponential function:
![$\displaystyle e^{\bf A}={\bf I}+{\bf A}+\frac{1}{2!}{\bf A}^2
+\frac{1}{3!}{\bf A}^3+\cdots$](img302.svg) |
(117) |
Specially when
is a diagonal matrix,
we have
![$\displaystyle e^{\bf\Lambda t}
={\bf I}+{\bf\Lambda t}+\frac{1}{2!}{\bf\Lambda}...
...&&e^{\lambda_Nt}
\end{array}\right]
=diag[e^{\lambda_1t},\cdots,e^{\lambda_Nt}]$](img304.svg) |
(118) |
The
coefficients in
can be found
based on the
given initial conditions
:
![$\displaystyle {\bf y}(0)={\bf y}(t)\bigg\vert _{t=0}
={\bf V}e^{{\bf\Lambda}t}{\bf c}\bigg\vert _{t=0}={\bf Vc}={\bf y}_0$](img307.svg) |
(119) |
Solving for
we get
.
Substituting this back to the general solution we get:
![$\displaystyle {\bf y}_h(t)={\bf V}e^{{\bf\Lambda}t}{\bf c}
={\bf V}e^{{\bf\Lambda}t}{\bf V}^{-1}{\bf y}_0$](img309.svg) |
(120) |
But as the eigenvalue and eigenvector matrices
and
of
satisfy
or
, we have
Therefore the homogeneous solution can be written as
![$\displaystyle {\bf y}_h(t)={\bf V}e^{{\bf\Lambda}t}{\bf V}^{-1}{\bf y}_0=e^{{\bf A}t}{\bf y}_0$](img317.svg) |
(122) |
Next, in the non-homogeneous case when
, the
complete solution of the first-order LCCODE system can again be
found analytically. We first multiply
on both sides
of the ODE
and get
![$\displaystyle e^{-{\bf A}t} {\bf y}'(t)-e^{-{\bf A}t}{\bf Ay}(t)
=\frac{d}{dt}\left[ e^{-{\bf A}t} {\bf y}(t) \right] =e^{-{\bf A}t}{\bf x}(t)$](img321.svg) |
(123) |
Integrating both sides we get
![$\displaystyle \int_0^t\frac{d}{d\tau}\left[ e^{-{\bf A}\tau} {\bf y}(\tau)\righ...
...-{\bf A}t}{\bf y}(t)-{\bf y}(0)
=\int_0^t e^{-{\bf A}\tau}{\bf x}(\tau) \;d\tau$](img322.svg) |
(124) |
Multiplying
on both side and rearranging we get
![$\displaystyle {\bf y}(t)=e^{{\bf A}t}{\bf y}(0)+e^{{\bf A}t}\int_0^t e^{-{\bf A...
...+\int_0^t e^{{\bf A}(t-\tau)}{\bf x}(\tau) \;d\tau\
={\bf y}_h(t)+{\bf y}_p(t)$](img324.svg) |
(125) |
where
is the homogeneous solution
same as that found previously, and
is the particular
solutions, the system response to the input
. Specially
when
is an impulse function, the system
response is the impulse response of the system:
![$\displaystyle {\bf y}_p(t)=\int_0^t e^{{\bf A}(t-\tau)}{\bf\delta}(\tau) \;d\tau=e^{{\bf A}t}$](img329.svg) |
(126) |
i.e., the particular solution is the convolution of the impulse response
and the input:
![$\displaystyle {\bf y}_p(t)=\int_0^t e^{{\bf A}(t-\tau)}{\bf x}(\tau) \;d\tau\
=e^{{\bf A}t}\,*\,{\bf x}(t)$](img330.svg) |
(127) |
The stability of the solution found above depends on the eigenvalues
. If they all have negative real part,
then the solution
is stable at it will always converge
to
. However, if one or more eigenvalues have positive real
parts while others have negative parts, a saddle point, then the
solution is unstable as it will approach
as
.
We next consider an Nth-order scalar ODE in the following
explicit form
![$\displaystyle \frac{d^N}{dt^N}y(t)=y^{(N)}(t)=f(t,\,y'(t),\cdots,y^{(N-1)}(t))$](img335.svg) |
(128) |
The goal is to find
satisfying this equation and some
given initial condition
. To solve this DE, we can
convert it into a first-order ODE system containing
first-order ODEs. Specifically, we define
(
) and represent these
functions in vector
form:
![$\displaystyle {\bf y}(t)=\left[\begin{array}{c}y_1(t)\\ y_2(t)\\ y_3(t)\\ \vdot...
...t)\\ y'_1(t)\\ y'_2(t)\\ \vdots\\ y'_{N-2}(t)\\ y'_{N-1}(t)
\end{array} \right]$](img338.svg) |
(129) |
so that the Nth-order ODE can be convered into
first-order
ODEs:
![$\displaystyle \frac{d}{dt}{\bf y}(t)={\bf y}'(t)
=\left[\begin{array}{c}y'_1(t)...
... \vdots\\ y_N(t)\\ f(t,\,{\bf y}(t))\end{array}\right]
={\bf f}(t,\,{\bf y}(t))$](img339.svg) |
(130) |
The last equation is the original Nth-order ODE:
Reconsider as an example the second order LCCODE in canonical
form:
![$\displaystyle y''(t)+2\zeta\omega_n y(t)+\omega_n^2 y(t)=x(t)$](img343.svg) |
(132) |
Here we first convert it into a first order equation system by
introducing
:
![$\displaystyle \left\{ \begin{array}{l}
y'_1=y'=y_2 \\
y'_2=y''=-2\zeta\omega_n y'-\omega_n^2y+x(t)
=-2\zeta\omega_ny_2-\omega_n^2y_1+x(t)
\end{array}\right.$](img345.svg) |
(133) |
or in matrix form
![$\displaystyle {\bf y}'(t)=\left[\begin{array}{c}y_1'(t)\\ y_2'(t)\end{array}\ri...
...ray}\right]
+\left[\begin{array}{c}0\\ x(t)\end{array}\right]
={\bf Ay}+{\bf x}$](img346.svg) |
(134) |
To solve this system, we first solve the eigenvalue problem of the
coefficient matrix
. Solving its characteristic equation:
![$\displaystyle \det(\lambda{\bf I}-{\bf A})
=\det\left[\begin{array}{cc}\lambda ...
...2\zeta\omega_n
\end{array}\right]
=\lambda^2+2\zeta\omega_n\lambda+\omega_n^2=0$](img347.svg) |
(135) |
we get the eigenvalues of
the two eigenvalues and the
eigenvalue matrix:
![$\displaystyle \lambda_{1,2}=\left(-\zeta\pm\sqrt{\zeta^2-1}\right)\omega_n
=\le...
...\Lambda}=\left[\begin{array}{cc}\lambda_1 & 0\\ 0 & \lambda_2\end{array}\right]$](img348.svg) |
(136) |
Note that
![$\displaystyle \lambda_1\lambda_2=\omega_n^2,\;\;\;\;\;\;\;\;\;\;
\lambda_2-\lambda_1=2\omega_n\sqrt{\zeta^2-1}$](img349.svg) |
(137) |
The corresponding eigenvectors can be found by solving the following
homogeneous equation:
![$\displaystyle (\lambda_i{\bf I}-{\bf A}) {\bf v}_i
=\left[\begin{array}{cc}\lam...
...rray}\right]
=\left[\begin{array}{c}0\\ 0\end{array}\right],\;\;\;\;\;\;(i=1,2)$](img350.svg) |
(138) |
to get
and
,
and
![$\displaystyle {\bf V}=\left[\begin{array}{cc}1 & 1\\ \lambda_1 & \lambda_2\end{...
...bda_1}
\left[\begin{array}{cc}\lambda_2 & -1\\ -\lambda_1 & 1\end{array}\right]$](img353.svg) |
(139) |
and we can verify thatat
. The general form
of the homogeneous solution is
![$\displaystyle {\bf y}=\left[\begin{array}{c}y_1\\ y_2\end{array}\right]
=c_1 {\...
...bda_1t}
+c_2\left[\begin{array}{c}1\\ \lambda_2\end{array}\right]e^{\lambda_2t}$](img354.svg) |
(140) |
i.e.,
![$\displaystyle \left\{
\begin{tabular}{l}
$y_1(t)=y(t)=c_1e^{\lambda_1t}+c_2e^{\...
...(t)=c_1\lambda_1e^{\lambda_1t}+c_2\lambda_2e^{\lambda_2t}$
\end{tabular}\right.$](img355.svg) |
(141) |
- Homogeneous case:
We have
and assume
and
.
Evaluating the general solution above at
, we get:
![$\displaystyle \left\{
\begin{tabular}{l}
$y_1(0)=y(0)=c_1+c_2=y_0$\\
$y_2(0)=y'_1(0)=c_1\lambda_1+c_2\lambda_2=0$
\end{tabular}\right.$](img358.svg) |
(142) |
Solving this we get
![$\displaystyle C_1=\frac{\lambda_2}{\lambda_2-\lambda_1}y_0,\;\;\;\;\;\;\;\;
C_2=\frac{\lambda_1}{\lambda_1-\lambda_2}y_0$](img359.svg) |
(143) |
Substituting into
above, we get:
![$\displaystyle y(t)=y_1(t)=\frac{y_0}{\lambda_2-\lambda_1}(\lambda_2e^{\lambda_1t}-\lambda_1e^{\lambda_2t})$](img361.svg) |
(144) |
Alternatively, we can also get
we get the same result as shown above:
![$\displaystyle y(t)=y_1(t)=\frac{y_0}{\lambda_2-\lambda_1}(\lambda_2e^{\lambda_1t}-\lambda_1e^{\lambda_2t})$](img361.svg) |
(145) |
- Nonhomogeneous case:
We assume
and zero initial conditions
,
i.e.,
and
, and get:
![$\displaystyle {\bf y}(t)=e^{{\bf A}t}{\bf y}(0)+e^{{\bf A}t}\int_0^t e^{-{\bf A}\tau}{\bf x}(\tau)d\tau
=e^{{\bf A}t}\int_0^t e^{-{\bf A}\tau} d\tau \;[0,\;1]^T$](img369.svg) |
(146) |
and
![$\displaystyle y_h(t)=y_1(t)=[1,\;0]\;{\bf y}(t)=[1,\;0]\; e^{{\bf A}t}\int_0^t e^{-{\bf A}\tau} d\tau\; [0,\;1]^T$](img370.svg) |
(147) |
where
![$\displaystyle \int_0^t e^{-{\bf A}\tau} d\tau=-{\bf A}^{-1} e^{-{\bf A}\tau}\bigg\vert _0^t
={\bf A}^{-1}( {\bf I}-e^{-{\bf A}t} )$](img371.svg) |
(148) |
Substituting
![$\displaystyle {\bf A}^{-1}=({\bf V\Lambda V}^{-1})^{-1}={\bf V\Lambda}^{-1}{\bf...
...t}{\bf V}^{-1},\;\;\;\;\;\;
e^{-{\bf A}t}={\bf V}e^{-{\bf\Lambda}t}{\bf V}^{-1}$](img372.svg) |
(149) |
into the function, we get
Example 2: A tuned mass-damper-spring system shown below is
described by the following ODEs:
![$\displaystyle \left\{\begin{array}{l}
My''=-Ky-Cy'-K_d(y-y_d)-C_d(y'-y_d')+f(t)\\
M_d y_d''=K_d(y-y_d)+C_d(y'-y_d')\end{array}\right.$](img377.svg) |
(150) |
This 2nd-order ODE system can be converted into a 1st-order ODE
system by introducing
and
:
![$\displaystyle \left\{\begin{array}{l}
y'=v\\
v'=[-Ky-Cy'-K_d(y-y_d)-C_d(y'-y_d')+f]/M\\
y_d'=v_d\\
v_d'=[K_d(y-y_d)+C_d(y'-y_d')/M_d\end{array}\right.$](img380.svg) |
(151) |
or in matrix form
![$\displaystyle {\bf y}'=
\left[\begin{array}{c}y'\\ v'\\ y_d'\\ v_d'\end{array}\...
...eft[\begin{array}{c}0\\ \frac{f}{M}\\ 0\\ 0\end{array}\right]
={\bf Ay}+{\bf x}$](img381.svg) |
(152) |
Specifically, if we assume
(modeling an earthquake)
i.e.,
, and all zero initial
condition
, then we get:
![$\displaystyle {\bf y}=\int_0^t e^{{\bf A}(t-\tau)}{\bf x}(\tau)d\tau$](img385.svg) |
(153) |
and
as the first component of
is
![$\displaystyle y(t)={\bf y}(1)={\bf v}_1^Te^{{\bf\Lambda}t}{\bf u}_2$](img387.svg) |
(154) |
where
and
are respectively the first row
of
and the second column of
.